Speaker notes for Painting, Petroleum and Neoliberalism in 1980: The energy unconscious at work in the ‘new spirit of painting’ - Carina Brand (2024)
The neoliberal era of the late 1970’s and early 1980’shas been characterised by swift and dramatic political economic reforms that rolled back the state, and followed an agenda of privatisation and financialisaton, however the discussion of how petroleum fits into the narrative of neoliberalism has only recently been developed. Following on from Timothy Mitchell, Matthew Huber and Caleb Wellum I concur that petroleum, as a specific form of energy is significant for the neoliberal project, as it firstly: created the atomised lifestyles of the post-war post-scarcity suburban life, secondly, created cultures around crisis, risk and ‘shocks’ that saw a need to return to the market and, thirdly supported an ongoing geopolitical investment in the petro-war machine. The focus of this paper will be the first two instances. With this re-evaluation of the role of petroleum in neoliberalism I propose that the return to painting, in what could be described as a global house style in the 1980’s, can be read as a cultural response to individualised petro-subjectivity and its simultaneous threat during the late 1970s and early 1980s.By illuminating connections between art, materiality, class and neoliberalism that have often been missed due to a focus on one at the expense of the other, we can propose that the major political economic shifts and class struggles of the period were interconnected by petroleum and simulated through painting. These discussions are couched in a wider discussion around what constitutes a petroleum aesthetic, following on from Stefanie LeMenager’s location of this aesthetic in the great American century, I assert that there is an important connection between post-war American identity and abstract expressionism, and that there is something in the role of expressive oil paint that links it with petroleum as material and ideology. Therefore, what we see in 1980’s expressive painting is not the development of a new aesthetic language but a reverting back to, albeit in Jameson’s postmodern terms, the language of the 1950s. I am interested in my wider research in connecting the speculative nature of petroleum, finance and painting. Each exists on the apex between the connection with a physical object and the imagination for something more. However, in this paper I will focus on the idea of an energy unconscious in painting and look more closely at three painters.